Using the Experience of the British Elite Boarding Schools «Public Schools» in Ukraine - Khaidari, Natalia (Pedagogical Discourse, 2017)
The article analyzes the private, including the elite, Education UK, which developed over the centuries and is a system that is tested and a history of successfully operating and is subject to strict high quality standards. The author studies the activities of British elite boarding schools «public schools» – elite boarding schools in the UK: Winchester College, Westminster School, Eton College, Rugby School, Harrow School, Charterhouse School, Shrewsbury School. An analysis of the state of private, in particular, elite, education in Ukraine has shown that, despite certain advances in this area, there is a need to improve the mechanisms that would help to remedy shortcomings in domestic educational practice. An impartial analysis of the situation shows that the problems faced by private schools are not accidental, they are of a systemic nature. To provide recommendations for the use in Ukraine of a constructive and progressive British experience in education in elite boarding schools, the reasons for the small distribution of private schools and boarding schools in Ukrainian pedagogical practice are revealed. According to the results of research to identify the organizational and educational foundations of the elite boarding schools in the UK to study the status of the problem in Ukraine, taking into account the identified deficiencies in domestic private education, we grounded recommendations for using British experience in the operation of private, including the elite, training Institutions of Ukraine – at legislative, scientific-methodical, educational-administrative and school levels. Practical recommendations for the introduction of the UK experience domestic enrich the theory and practice of education of gifted students, which can be the basis for further research in this area.